The Effect of Transformational Leadership and Organizational Culture on The Quality of Education Services - Furtasan Ali Yusuf; Anis Fauzi; Anwar Malik (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
The main problems in this study are: (1) Is there a significant effect of transformational leadership on the quality of education services ?; (2) Is there a significant influence of organizational culture on the quality of education services? (3) Is there a significant influence of transformational leadership and organizational culture together on the quality of education services in Islamic Elementary School in Serang City? The method used in this research is a correlational quantitative method with a questionnaire research instrument. This research was conducted at Islamic Elementary School in Serang City, with a population of 207 and 82 respondents as the sample in the study. The results of this study indicate that: (1) transformational leadership can influence the formation of the quality of education services, with a correlation coefficient of